Three new species of Xenotarsonemus (Acari: Tarsonemidae) from the northwestern region of São Paulo State, Brazil - Pitton, Thafarel; Lofego, Antonio C.; Rezende, José M. (Zootaxa, 2016)
Three new species of Xenotarsonemus Beer (Acari, Tarsonemidae), X. demitei n. sp., X. kaingang n. sp. and X. luziae n. sp., are described based on specimens collected from plants in native vegetation in the northwestern region of the São Paulo State, Brazil.